Los desequilibrios regionales en España - Franco Aliaga, Tomás (Espacio Tiempo y Forma. Serie VI, Geografía, 1990)
Regional inequialities have always existed as can be steen throughout Spanish Economic History. Until well into the Modern Age, inland Spain contained two tliirds of tlie population and yielded most of tlie resources. However, the capitalist system and the free market exarcerbate such inequalities because of their own dynamics, polarizing resources in order to obtain the highest profit. The consequences of this, seen from the geographical point of view, are a migrant population, environnnental changes, urban growth, and the adoption of new forma of spatial organization, among others. Between 1960-1973 the country witnessed a «miraculous» economic growth rate and as such there was a widespread and significant backward movement with important effects in the more industrially developed regions. The economic recovery (1986-1989) maintains such inequalities although the development axes spread in a «4» form which embraces the Valle del Ebro (Ebro Valley), the mediterranean arch from Gerona (Nort Cataluña) to Málaga (South-East Andalucía) and both archipielagos and Madrid, which still is the well established reference point in present-day Spain and its autonomous regions.